The prevalence of back pain in patients in one Australian tertiary hospital population. - Dennis, D.; Tampin, B.; Jacques, Angela; Hebden-Todd, T.; Carter, V.; McLintock, M.; Hurn, E.; Cooper, I. (2017)
Objectives: The aims of the present study were to provide back pain (BP) point prevalence data from inpatients at an Australian tertiary hospital on one day, and compare this with Australian non-hospitalized population prevalence data; to collect data around the development of BP throughout hospital admission; and to analyse the association between BP and past history of BP, gender, age, admission specialty and hospital length of stay (LOS). Methods: This was a single-site, prospective, observational study of hospitalized inpatients on one day during 2016, with a subsequent survey over the following 11 days (unless discharge or death occurred sooner). Results: Data were collected from 343 patients (75% of the hospitalized cohort). A third of patients (n = 108) reported BP on admission, and almost a fifth (n = 63) developed new BP during their hospitalization. Patients who described BP at any time during their hospital stay had a higher chance of having had a history of BP, with odds increasing after adjustment for age and gender (odds ratio 5.89; 95% confidence interval (CI) 3.0 to 11.6; p < 0.001). After adjusting for age and gender, those experiencing BP had a significantly longer LOS (median 13 days; CI 10.8 to 15.3) than those who did not (median 10 days; CI 8.4 to 11.6; p = 0.034). Conclusions: Hospital LOS for patients who complained of BP at any time during their admission was 3 days longer than those who had no BP, and a history of BP predicted a higher likelihood of BP during admission. Screening of patients on admission to identify any history of BP, and application of a package of care including early mobilization and analgesia may prevent the onset of BP and reduce LOS.